Development of an Instructional Model based on Character Education and Experiential Learning Approaches for Enhancing Cultural Competences in Nursing of Nursing Students - อารยะธนิตกุล, บุศย์รินทร์; เสวกงาม, วิชัย; ชูชาติ, อลิศรา (Journal of The Royal Thai Army Nurses, 2017)
This research and development study aimed to develop an instructional model for enhancing cultural competences in nursing of nursing students and evaluate the achievement of the model which consisted of 2 phases. The frst phase was the development of an instructional model by using character education and experiential learning approaches. The second phase was the use of the instructional model and the evaluation of achievement. The instructional model was used to teach 21 third year students in Bachelor’s Degree of Nursing Program. In this case, the students were studying in the Pediatric practicum course in the frst semester of academic year 2016. The employed research instruments were cultural competency assessment form, alearning log and a study of patient’s culture form. Data were analyzed using percentage, mean, standard deviation and T-test. The results of study were 1. The instructional model for enhancing cultural competences in nursing of nursing students was composed of four steps as follows: learning by clinical practicing based on ethics, reﬂecting and sharing, formulating good practice and good characters and practicing based on good practice and characters. 2. The result from using of the instructional model showed that after the experiment, the students had the higher of cultural competence scores in cultural awareness, ability to gain knowledge about culture, and cultural care skills at the statistically signifcant level of .05. Students are conscious and valued culture, gathered cultural data completely, planed congruent care for the patients and practiced with empathy, honor and respect.